2017
DOI: 10.1021/acs.inorgchem.7b00014
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Some Layered U2O5 Phases: A Density Functional Theory Study

Abstract: UO is the boundary composition between the fluorite and the layered structures of the UO system and the least studied oxide in the group. δ-UO is the only layered structure proposed so far experimentally, although evidence of fluorite-based phases has also been reported. Our DFT work explores possible structures of UO stoichiometry by starting from existing MO structures (where M is an actinide or transition metal) and replacing the M ions with uranium ions. For all structures, we predicted structural and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…The latter study showed that it is possible to stabilize fluorite-like normalU3normalO8 at high temperature and pressure, which is retained upon quenching to ambient conditions. This experimental work is further supported by theory calculations (16, 17), which indicate that stoichiometries up to normalUnormalO2.5 should be possible within the fluorite-like structure. Together, these studies suggest that the primary impact of excess oxygen will be on the type and distribution of O anion defects, rather than a sizable distortion of the U cation sublattice.…”
supporting
confidence: 68%
“…The latter study showed that it is possible to stabilize fluorite-like normalU3normalO8 at high temperature and pressure, which is retained upon quenching to ambient conditions. This experimental work is further supported by theory calculations (16, 17), which indicate that stoichiometries up to normalUnormalO2.5 should be possible within the fluorite-like structure. Together, these studies suggest that the primary impact of excess oxygen will be on the type and distribution of O anion defects, rather than a sizable distortion of the U cation sublattice.…”
supporting
confidence: 68%
“…A similar approach has been used by Molinari et al . 47 to compare the relative stability of various candidate structures for U 2 O 5 . These authors conclude that the most stable U 2 O 5 structure is the Np 2 O 5 -type monoclinic one (containing uranyl square and pentagonal bipyramids linked by edge-sharing into sheets), whereas δ-U 2 O 5 would become energetically favoured only at high temperatures or pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The DFT work from Molinari et al 25 predicted that the Np 2 O 5 -structured U 2 O 5 is the most stable among those considered under ambient conditions. However, the observed d-U 2 O 5 structure is found to be the second most stable.…”
Section: Stabilitymentioning
confidence: 99%
“…In the actinide elements, uranium (U) exhibits rich oxide phases, such as UO 2 , U 2 O 3 , U 2 O 5 , and U 3 O 8 , [20][21][22][23][24][25][26][27] and its two prominent oxidation states are U 4+ and U 6+ . Plutonium (Pu) has stable Pu 4+ , Pu 5+ , and Pu 6+ oxidation states in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%